Expression of human‐specific ARHGAP11B in mice leads to neocortex expansion and increased memory flexibility. (3rd May 2021) - Xing, Lei; Kubik‐Zahorodna, Agnieszka; Namba, Takashi; Pinson, Anneline; Florio, Marta; Prochazka, Jan; Sarov, Mihail; Sedlacek, Radislav; Huttner, Wieland B
Abstract: Neocortex expansion during human evolution provides a basis for our enhanced cognitive abilities. Yet, which genes implicated in neocortex expansion are actually responsible for higher cognitive abilities is unknown. The expression of human‐specific ARHGAP11B in embryonic/foetal mouse, ferret and marmoset neocortex was previously found to promote basal progenitor proliferation, upper‐layer neuron generation and neocortex expansion during development, features commonly thought to contribute to increased cognitive abilities. However, a key question is whether this phenotype persists into adulthood and if so, whether cognitive abilities are indeed increased. Here, we generated a transgenic mouse line with physiological ARHGAP11B expression that exhibits increased neocortical size and upper‐layer neuron numbers persisting into adulthood. Adult ARHGAP11B ‐transgenic mice showed altered neurobehaviour, notably increased memory flexibility and a reduced anxiety level. Our data are consistent with the notion that neocortex expansion by ARHGAP11B, a gene implicated in human evolution, underlies some of the altered neurobehavioural features observed in the transgenic mice, such as the increased memory flexibility, a neocortex‐associated trait, with implications for the increase in cognitive abilities during human evolution. Synopsis: In transgenic mice, the neocortex expansion and increased neuron numbers induced by physiological expression of human‐specific ARHGAP11B persist into adulthood. Adult ARHGAP11B‐transgenic mice exhibit increased memory flexibility and reduced anxiety. Expression of human‐specific ARHGAP11B at a physiological level in transgenic mouse embryos results in increased basal progenitor proliferation and abundance. ARHGAP11B‐transgenic mouse embryos show increased neocortex size and neuron numbers. Cortical expansion and increased upper‐layer neuron numbers in ARHGAP11B‐transgenic mice persist into adulthood. Adult ARHGAP11B‐transgenic mice exhibit altered neurobehaviour, notably increased memory flexibility and reduced anxiety. Abstract : Effects of human‐specific ARHGAP11B, linked to higher cognitive abilities, on basal progenitor proliferation and upper‐layer neuron generation in rodent embryos persist into adulthood, correlating with altered neurobehaviour including reduced anxiety levels.